Windows Server administration fundamentals - Panek, Crystal (Sybex, a Wiley brand, 2020)
Did you know, 91% of hiring managers consider certification as part of their hiring requirements? IT Professionals who are new to the industry need a strong foundational understanding of the fundamentals before moving on towards more challenging technology certifications. This book covers everything you need to know about understanding how to manage windows servers and storage along with monitoring and troubleshooting servers as well. Written to the Windows Server Administration Fundamentals MTA Certification, it is a recommended entry point into IT certification. This book covers the basics of Windows Server Administration. Each chapter closes with a quiz to make sure you can practice exam questions and test your knowledge begore moving to the next section. We start by discussing what a server is and does by providing an in-depth overview including installation of Windows Server 2016. There are sections dedicated to the following: Preforming configurations and managing your Windows Server, by configuring your IP address settings and managing devices and device drivers. Managing your storage, by identifying storage technologies, understanding disk structure, and using disk management tools. Monitoring and troubleshooting servers, by managing information technology, and understanding performance, backups and preforming server repair. Overview of popular Windows network services and applications, like understanding remote access, server virtualization, and introducing remote administration. IT Professionals looking to understand more about Windows Server Administration will gain he knowledge to effectively install and manage a Windows Server including basic troubleshooting. Thanks to some troubleshooting tools and tops it will be easier to apply the skills in real world situations and feel confident when taking the certification.